Content-analysis of educational and work programs on the military psychology discipline in higher educational institutions of Ukraine in the 21st century - Pylypchuk, Yaroslav (ScienceRise: Pedagogical Education, 2026)
This article is devoted to the content analysis of educational and work programs on the discipline «Military Psychology» in higher educational institutions of Ukraine in the 21st century. Military education has gone through several stages in its development. Before the Russian invasion of Eastern Ukraine (ATO), curricula and work programs were informational support for peacetime. The Russian invasion of Eastern Ukraine led to the occupation of part of the Donbass territory. The experience of this conflict was taken into account by Ukrainian researchers in the second half of the 10s of the 21st century. The practical experience of Ukrainian military educators and military psychologists, as well as the work of foreign educators, was involved. A number of curricula and work programs, as well as syllabi, were developed. The full-scale Russian invasion of Ukraine led to a new stage in the study of military psychology and military pedagogy. This conflict is high-tech, since UAVs are used. At the moment, the best program is the work program developed by O. Shevyakov in 2023 at the Dnipro University of Internal Affairs. The experience of the Russian-Ukrainian war, in the author’s opinion, will allow for a qualitative breakthrough in the field of military psychology and military pedagogy. The curricula will be enriched with the practical experience of military psychologists who participated in a high-intensity conflict. It is worth noting that the Russian-Ukrainian war is the largest conflict since World War II. Another of its features is its high technological content, in particular the use of drones. It is worth noting that the more technological the war, the greater its impact on the psyche of its participants. Military psychologists will have experience working with a wide range of psychogenic disorders in war veterans